Clinicopathological correlation of cerebrospinal fluid alpha‐synuclein seed amplification assay in a behavioral neurology autopsy cohort - Samudra, Niyatee; Fischer, D. Luke; Lenio, Steven; Lario Lago, Argentina; Ljubenkov, Peter A.; Rojas, Julio C.; Seeley, William W.; Spina, Salvatore; Staffaroni, Adam M.; Tablante, Jonathan; Wekselman, Fattin; Lamoureux, Jennifer; et al. (Alzheimer's & dementia, 2024)
INTRODUCTION Lewy body disease (LBD) is a common primary or co‐pathology in neurodegenerative syndromes. An alpha‐synuclein seed amplification assay (αSyn‐SAA) is clinically available, but clinical performance, especially lower sensitivity in amygdala‐predominant cases, is not well understood. METHODS Antemortem CSF from neuropathology‐confirmed LBD cases was tested with αSyn‐SAA (N = 56). Diagnostic performance and clinicopathological correlations were examined. RESULTS Similar to prior reports, sensitivity was 100% for diffuse and transitional LBD (9/9), and overall specificity was 96.3% (26/27). Sensitivity was lower in amygdala‐predominant (6/14, 42.8%) and brainstem‐predominant LBD (1/6, 16.7%), but early spread outside these regions (without meeting criteria for higher stage) was more common in αSyn‐SAA‐positive cases (6/7, 85.7%) than negative (2/13, 15.4%). DISCUSSION In this behavioral neurology cohort, αSyn‐SAA had excellent diagnostic performance for cortical LBD. In amygdala‐ and brainstem‐predominant cases, sensitivity was lower, but positivity was associated with anatomical spread, suggesting αSyn‐SAA detects early LBD progression in these cohorts. Highlights A cerebrospinal fluid alpha‐synuclein assay detects cortical LBD with high sensitivity/specificity. Positivity in prodromal stages of LBD was associated with early cortical spread. The assay provides precision diagnosis of LBD that could support clinical trials. The assay can also identify LBD co‐pathology, which may impact treatment responses.